The Impact of The Philosophy of History on The Nature of Constitutional Legislation In Iraq (The 2005 Constitution of The Republic of Iraq As A Model) (Journal of the College of Basic Education, 2026)
Philosophy of History is a recently emerged branch of the humanities that relies on a holistic view of events, seeking their causes and ultimate purposes. It aims to extract wisdom and lessons for the present while viewing history not merely as past events, but as a bridge to the future.This research illustrates the robust relationship between the philosophy of history and future legislation in Iraq. It proceeds from the premise that this relationship is built on interconnection, mutual influence, and the dialectical negation of old ideas by emerging concepts in the pursuit of evolution and progress. By analyzing the 2005 Constitution of the Republic of Iraq as a model, the study seeks to demonstrate the interaction between the past and present and to envision the future.The research is based on the hypothesis that constitutions are not drafted in a vacuum; rather, they are shaped by a collective historical consciousness that carries the imprints of previous experiences. These constitutions aspire to transcend past struggles through deliberate legislation that accounts for historical lessons while anticipating future horizons.The study employs an analytical-hermeneutical method, supported by a historical-philosophical approach, to reveal how historical memory is present within the Iraqi constitutional text and its capacity to guide future legislation and state-building.